First results from MFOSC-P: low-resolution optical spectroscopy of a sample of M dwarfs within 100 parsecs - Rajpurohit, Arvind Singh; Kumar, Vipin; Srivastava, Mudit K.; Homeier, Derek (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Mt Abu Faint Object Spectrograph and Camera (MFOSC-P) is an in-house-developed instrument for the Physical Research Laboratory (PRL) 1.2 m telescope